Adherence to guidelines on the use of amoxicillin for treatment of ambulatory pneumonia in children younger than 5 years, Colombia, 2017–2019 - Luisa Moyano Ariza; Brindis Ochoa; Hemant D. Shewade; Jeffrey K. Edwards; Julián Trujillo Trujillo; Claudia M. Cuellar; Jaime Rodríguez; Katrina Hann; Mauro Sanchez (Revista Panamericana de Salud Pública, 2023)
Objectives. To determine the level of adherence to clinical guidelines in prescribing amoxicillin to children younger than 5 years with pneumonia in outpatient settings in Colombia from 2017 to 2019, and assess the factors associated with adherence Methods. This was a cross-sectional study of secondary data from the Colombian Integrated Social Protection Information System database. Adherence was defined as prescription of oral amoxicillin for bacterial and unspecified pneumonia and non-prescription for viral pneumonia. Variables examined included: age (< 1 year, 1–4 years) of child; sex; cause of pneumonia (bacterial, viral, unspecified); region (Andean, Amazonian, Pacific, Caribbean, Insular, Orinoquian); and payment mechanism (without prior authorization, capitation, direct payment, pay per case, pay for event). Results. Of 215 925 cases of community-acquired pneumonia reported during 2017–2019, 64.8% were from the Andean region, 73.9% were bacterial pneumonia and 1.8% were viral pneumonia. Adherence to guidelines was observed in 5.8% of cases: this was highest for children diagnosed with viral (86.0%) compared with bacterial (2.0%) pneumonia. For children diagnosed with bacterial pneumonia, 9.4% were prescribed any antibiotic. A greater proportion of children covered by capitated payments (22.3%) were given treatment consistent with the guidelines compared with payment for event (1.3%). Conclusion. In this first study from Colombia, adherence to guidelines for outpatient treatment of children with bacterial pneumonia was low and was better for viral pneumonia. Further qualitative studies are needed to explore the reasons for this lack of adherence and why bacterial pneumonia was the most commonly reported etiology.